Perbandingan Metode Exponential Smoothing Untuk Peramalan Penjualan Produk Olahan Daging Ayam Kampung (Studi Kasus : Ayam Goreng Mama Arka) - Dzar Romaita; Fitra Abdurrachman Bachtiar; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ayam Goreng Mama Arka is a culinary business of Ayam Kampung meat products that are currently developing. Uncertain customer demand is a challenge for Ayam Goreng Mama Arka to determine the right sales strategy in order to maximize profits and minimize losses Therefore, a customer demand forecasting system is made using the Exponential Smoothing method. In this research, comparing the accuracy of 3 methods of Exponential Smoothing, namely: Single Exponential Smoothing (SES), Double Exponential Smoothing (DES), and Triple Exponential Smoothing (TES) using Mean Absolute Error (MAE). The data used are sales results from January 2019 to November 2019 for 5 products,namely ayam goreng laos, ayam bakar kecap, ayam bumbu rujak, ayam frozen laos, and ayam frozen rujak. Based on the test results for one of the products namely ayam bakar kecap, the smallest value obtained in TES method when a=0.3, b=0.2, g=0.7 with value of 2.45, while the largest MAE value obtained in DES method when a=0.3, b=0.1 with value of 2.74. Overall, forecasting with TES show the best result for 3 products, the smallest MAE value is 2.45 which obtained in ayam bakar kecap products, so it can be concluded that the most accurate method for forecasting ayam kampong meat products is the Triple Exponential Smoothing method.